Belonging in a New Myanmar: Identity, Law, and Gender in the Anthropology of Contemporary Buddhism - Schober, Juliane (Religion and society, 2017)
"To be Burmese is to be Buddhist" is a slogan commonly identified with the dawn of nationalism in the country known today as Myanmar, where violence between Buddhist, Muslim, and ethnic communities has increasingly jeopardized liberalizing reforms. How do contemporary forms of Theravada Buddhist discourse shape ideas of belonging in a multi-religious and ethnically diverse Myanmar following the dissolution of military rule in 2011? How do digital technologies and globalizing communication networks in this nation influence rapidly changing social identities, anxieties, and imaginaries that Brigit Meyer identifies as "aesthetic formations"? In this article, I trace diverse genealogies of belonging to show how contemporary constructions of meaning facilitate religious imaginaries that may exacerbate difference by drawing on past ideologies of conflict or may seek to envision a new and diverse Myanmar.